Partial-Purification of a Virus-Associated with a Spanish Isolate of Citrus Ringspot - Navas-Castillo, J.; Moreno, Pedro; Cambra, Mariano; Derrick, K. (2017)
A citrus ringspot isolate from Star Ruby grapefruit (RS-SR) was mechanically transmitted to Chenopodium quinoa. RS-SR was partially purified by differential centrifugation, fractionation in a sucrose gradient, and agarose gel electrophoresis of selected fractions. Infectivity of concentrated extracts on C. quinoa was lost in individual fractions of the gradient, but it was recovered by combining a top and a bottom component. Both components contained a 48-kDa protein not found in similar preparations from healthy plants. After further purification the 48 kDa protein was detected at the top edge of the agarose gel. In the initial experiments a 38-kDa protein was found in the same fractions that later contained the 48-kDa protein. An antiserum obtained to the 38 kDa protein reacted in Western blots with both the 38- and the 48-kDa proteins, whereas another antiserum raised to the Florida isolate CRSV-4 (also containing a 48-kDa protein) did not react with the 38-kDa protein, indicating that the latter was probably a degradation product of the 48-kDa protein. Filamentous flexous particles were observed by serologically specific electron microscopy in crude extracts from RS-SR-infected C. quinoa plants. These results indicate that RS-SR is associated with a two-component virus similar to those associated with several psorosis and ringspot isolates, and serologically related to CRSV-4.